2019
DOI: 10.33893/fer.18.2.5286
|View full text |Cite
|
Sign up to set email alerts
|

Performance Measurement of Active Investment Strategies Using Pure Factor Portfolios

Abstract: The article uses pure factor portfolios formed by multivariate cross-sectional regressions to examine whether these active investment strategies could achieve excess return relative to passive strategies. The hypothesis can also be construed as a test of market efficiency. The study includes ten style factors. Our empirical study shows that a consensus buy strategy of the pure value factor yielded significant positive excess returns in the past almost 20 years. Size and momentum factors characterised in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…By and large, impact investments display a wide dispersion of returns, attributable to factors such as asymmetrical information, manager selection and inconsistent investor objectives (Mudaliar & Bass, 2017;Jeffers et al, 2021;Bernal et al, 2021). Divergent perspectives relate to studies such as those by (Fain & Naffa, 2019;Blankenberg & Gottschalk, 2018) that describe a no-effect hypothesis between ESG and financial return performance. Blankenberg and Gottschalk (2018) reported equivalent performance relative to a traditional portfolio, while Naffa and Fain (2022) concluded that ESG ratings serve to quantify sustainability risks.…”
Section: Resultsmentioning
confidence: 99%
“…By and large, impact investments display a wide dispersion of returns, attributable to factors such as asymmetrical information, manager selection and inconsistent investor objectives (Mudaliar & Bass, 2017;Jeffers et al, 2021;Bernal et al, 2021). Divergent perspectives relate to studies such as those by (Fain & Naffa, 2019;Blankenberg & Gottschalk, 2018) that describe a no-effect hypothesis between ESG and financial return performance. Blankenberg and Gottschalk (2018) reported equivalent performance relative to a traditional portfolio, while Naffa and Fain (2022) concluded that ESG ratings serve to quantify sustainability risks.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above approach, stock exchanges are drivers of economic growth, which can result in environmental pollution. Stock exchanges are important barometers of economies; the good performance of a stock exchange implies fast economic growth and the increase of the general welfare of society (Fain-Naffa, 2019;Jiang-Ma, 2019). Welfare boosts the consumption of businesses and consumers alike leading to increased energy consumption and carbon emissions as business activities proliferate (Sadorsky, 2010;Sadorsky, 2011;Mankiw-Scarth, 2008).…”
Section: Effects and Counter-effectsmentioning
confidence: 99%
“…For the most part, this subchapter rests on the work ofFain and Naffa (2019) (Fain, M., Naffa, H., 2019…”
mentioning
confidence: 99%